Data Collection Tool for Olive Oil Market Monitoring / Outil de Collecte de Données pour le Suivi du Marché de l'Huile d'Olive - Ouerghemmi, Hassen; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
This XLS (FR) form is programmed into the mobile data collection tool (ODK) and used by agents of the Office National de l'Huile in Tunisia to collect data relating to the olive and olive oil market in 2023/2024.